Dança e transformação: a potencialidade terapêutica do corpo em movimento - Brito, Rafaella Medeiros de Mattos (2019)
This research explored how dance, in the context of therapeutic groups, unveiled new possibilities for personal transformation. The objective of this research was to identify and understand which therapeutic processes are experienced in approaches that focused on dance and movement, thus promoting beneficial changes for those who practiced them. In this context, the main fields studied were Somatic Education, Dance Movement Therapy and Biodança. Therefore, the study started from the exploration of these fields. Posteriorly, two interview cycles were used with professionals and clients from different therapeutic practices from both psychotherapeutic approaches and non-psychotherapeutic approaches. A third data source was the researcher’s field diary notes regarding her participation into a therapeutic dance group. In addition to the basic principles of Somatic Education, Dance Movement Therapy and Biodança; its theoretical reference also included the Experiential Theory of Eugene Gendlin and the philosophy of Merleau-Ponty. Thus, the contribution of these authors leads to the core presupposition of this research i.e. the belief in a body wisdom. This principle supported theoretical discussion of new therapeutic pathways triggered and directed by the dancing body, beyond and above speech. Regarding the research methodology, the Interactive Methodology from Oliveira (2001, 2011) was used as reference. Subsequently, the data collection was based on the methods of hermeneutic-dialectical circle and field diary. The data were then submitted to Dialectic Hermeneutic Analysis, proposed by Minayo (2010). Finally, research results, based on the similarities found in practical experiences and considering the theoretical reference adopted, showed seven major therapeutic processes identified in practices that work with dance and movement. These were: perception, symbolization, encounter and communication, processing and integration, association and metaphors, evocation of memories, totality and connection. In conclusion, the research shows that different transformation processes occur from a dance-based therapy and a talking cure therapy, so that each individual should choose the therapeutic practice that best fits each style and need.